Avaliação método único de preparo de amostras para determinação de microplásticos e halogênios em frutos do mar - Almeida, Débora Pereira de (2022)
The purpose of this work is to develop a method for microplastics (MPs) determination in fish tissue using a selective digestion of fish tissue without damaged MPs. A simple approach was developed using alkaline reagents and microwaveassisted wet digestion, allowing both MPs and halogens in the same digests by gravimetry (MPs) and inductively coupled plasma optical emission spectrometry (ICP-OES) and ion chromatography (IC). For this, up to 2 g of fish sample (shark specie) was spiked with 0.1 g of a mix of MPs (polyethylene terephthalate (PET), polystyrene (PS), expanded polystyrene (EPS), polypropylene (PP), high-density polyethylene (HDPE), low-density polyethylene (LDPE), polycarbonate (PC), and polyvinyl chloride (PVC)). The digestion parameters evaluated were: alkaline digestion solutions (0.1 mol L-1 NH4OH, 10% w/v NaOH, 0.1 mol L-1 KOH, and 0.1 mol L-1 TMAH), digestion temperature (30 °C to 200 °C), and sample mass (0.5 to 2 g). After decomposition, the digests were filtered (pore size lower than 2 μm, Whatman No. 589/3 Florham Park, MI) and the MPs content was gravimetrically determined. Suitable conditions were obtained using 0.1 mol L-1 NH4OH at 180 °C and 20 min of heating time, making possible to digest up to 1.5 g of in natura sample, without retained particles in the filtration process. The recovery of MPs was from 93 to 98%. The proposed method allowed the gravimetric determination of seven from the eight types of plastics (PET, PS, EPS, PP, HDPE, LDPE, PC and PVC) with particle size higher than 0.5 mm. Because of the good aspect of digestion soluition (without suspended particles), the suitability of the proposed method for MPs determination was evaluated for halogens determination (F, Cl, Br, and I). The results obtained showed that it was possible to use the same digest solition for halogen determination using ICP-OES (Cl) and ICP-MS (Cl, Br and I) techniques. Furthermore, the agreement obtained for the CRM of fish tissue using the method protocol was 80% for Cl and Br, and 91% for I. It was evaluated the Cl recovery from spiking known concentrations of NaCl, which presented recoveries in the range of 72-84%. Therefore the proposed method can be considered suitable for the determination of seven of the eight variations of MPs evaluated in fish tissue. The proposed method can be considered suitable for the determination of seven types of MPs in fish tissue. Besides, the same digest used for MPs determination can be used for the determination of Cl, Br, I e F providing accurate and precise information about MP and halogens.